SECURE CLUSTERING AND TRUSTWORTHY ROUTING PROTOCOL IN WIRELESS SENSOR NETWORKS - Mukesh Kumar Singh (International Journal of Multidisciplinary Research and Studies, 2021)
Wireless Sensor Networks, also known as WSNs, are gaining in popularity as a potentially useful technology owing to the diverse array of applications that may be carried out using them. This is one of the reasons why they are called "WSNs." The monitoring of the environment is only one of many applications; others include those in the industrial, military, and civilian domains respectively. On the other hand, it is vulnerable to a wide variety of attacks of different sorts. The adversary was successful in compromising a node, which led to the loss of all data packets that were routed through that node. The data packets were lost as a consequence of the node being compromised. The amount of energy that can be pulled from batteries places severe limitations on the performance of sensor nodes, which in turn decreases the network's durability and overall quality. Because of this, it is very necessary for wireless sensor networks (WSNs) to make the most of the lifetime of their nodes and minimize the amount of bandwidth they require by coordinating locally among sensor nodes.